The Neurobehavioral Effects of Buprenorphine and Meloxicam on a Blast-Induced Traumatic Brain Injury Model in the Rat - Anderson, Laura M.; Samineni, Sridhar; Wilder, Donna M.; Lara, Marisela; Eken, Ondine; Urioste, Rodrigo; Long, Joseph B.; Arun, Peethambaran (Frontiers in Neurology, 2021)
Previous findings have indicated that pain relieving medications such as opioids and non-steroidal anti-inflammatory drugs (NSAIDs) may be neuroprotective after traumatic brain injury in rodents, but only limited studies have been performed in a blast-induced traumatic brain injury (bTBI) model. In addition, many pre-clinical TBI studies performed in rodents did not use analgesics due to the possibility of neuroprotection or other changes in cognitive, behavioral, and pathology outcomes. To examine this in a pre-clinical setting, we examined the neurobehavioral changes in rats given a single pre-blast dose of meloxicam, buprenorphine, or no pain relieving medication and exposed to tightly-coupled repeated blasts in an advanced blast simulator and evaluated neurobehavioral functions up to 28 days post-blast. A 16.7% mortality rate was recorded in the rats treated with buprenorphine, which might be attributed to the physiologically depressive side effects of buprenorphine in combination with isoflurane anesthesia and acute brain injury. Rats given buprenorphine, but not meloxicam, took more time to recover from the isoflurane anesthesia given just before blast. We found that treatment with meloxicam protected repeated blast-exposed rats from vestibulomotor dysfunctions up to day 14, but by day 28 the protective effects had receded. Both pain relieving medications seemed to promote short-term memory deficits in blast-exposed animals, whereas vehicle-treated blast-exposed animals showed only a non-significant trend toward worsening short-term memory by day 27. Open field exploratory behavior results showed that blast exposed rats treated with meloxicam engaged in significantly more locomotor activities and possibly a lesser degree of responses thought to reflect anxiety and depressive-like behaviors than any of the other groups. Rats treated with analgesics to alleviate possible pain from the blast ate more than their counterparts that were not treated with analgesics, which supports that both analgesics were effective in alleviating some of the discomfort that these rats potentially experienced post-blast injury. These results suggest that meloxicam and, to a lesser extent buprenorphine alter a variety of neurobehavioral functions in a rat bTBI model and, because of their impact on these neurobehavioral changes, may be less than ideal analgesic agents for pre-clinical studies evaluating these neurobehavioral responses after TBI.